Overtraining research advances in China - Bu, B.; Su, Q.; Sun, J. (Journal of Exercise Science & Fitness, 2003)
Overtraining is one of the main problems in sports in China. In order to better understand and prevent overtraining, experimental studies conducted in this research field in China were reviewed. The aspects of fatigue, overstrain (overstress), overtraining, overtraining-related syndromes, and recovery were discussed. Since 1980s, overtraining has been studied extensively from the perspectives of hematology, biochemistry, immunology, and biomechanics via the methods of Evidence Based Medicine and Meta analysis. Herbal medicine to treat overtraining and facilitate recovery were the major themes of studies conducted in China. To deal with the overtraining and the myriad of health conditions produced because of overtraining, a multiple factorial approach is needed, which includes successful preventive medicine, nutrition supporting, optimal monitor marker selection, and efficacious rehabilitation therapy. All of these approaches require a thorough understanding of fundamental biology and how the dysregulated molecular circuitry caused by overtraining produces the relevant syndrome. It is shown that the pathological changes of overtraining could happen in different levels from organ to expression of genome. Herbal medicines, Chinese massage and Qigong therapy were considered to be effective treatments for overtraining.